Percepções de pesquisadores brasileiros sobre o acesso aberto à literatura científica - Furnival, Ariadne Chloe Mary; Silva-Jerez, Nelson Sebastian [UNESP] (My University, 2017)
The research aimed to explore how various dimensions of open access to scientific literature is perceived by Brazilian researchers, also identifying their habits of publication, as well as use and citation of sources in open access. The methodological approach was quantitative, using a survey developed in the open software, Lime Survey, and consisting of 29 closed questions, responded by 643 permanent doctors from Brazilian universities distributed in all subject areas. Surveys completed by researchers from 31 Institutes of Higher Education and Research Institutes in Brazil were received. Stratification by area showed a relatively balanced distribution between knowledge fields, with the largest percentage being from the Health Sciences (21%), followed by the Physical and Earth Sciences (20.1%) and the lowest percentage of 1.1% from Linguistics, Literature and Arts. The results indicate that the vast majority of participating researchers has knowledge of and support for, open access principles and some projects promoting it, especially in relation to open access journal publishing, which also reflects in their usage habits and citation of such sources. Comparatively, the knowledge and use of open access repositories is smaller, and there seems to be some confusion regarding copyright status of archived articles in repositories. It was evident that the researchers believe that only postprints should be available in repositories. Ignorance identified regarding the compatibility between publication in conventional subscription journals, and deposit of the same article in open access repositories indicates the need for greater informative initiatives to clarify these aspects.
Brazilian researchers views on open access to scientific literature
Keywords: Communication; Open access; Opinions; Scientific publication; Scientific researchers